Implementation of Indonesia Ship Reporting System (IndoSRep) in the Archipelagic Sea Lanes Passage of Indonesia (ALKI) - Mantoro, Budi; Indrawan, Rully; Octora, Theresya Yoanyta; Saputra, Datep (KnE Social Sciences, 2025)
As an archipelagic country, Indonesia holds a highly strategic position in international trade and shipping routes. This is reflected in the Indonesian archipelagic sea lanes (ALKI) designation as primary shipping routes connecting international waters in the Southeast Asian region and the Pacific Ocean. However, the high intensity of vessel traffic in these waters poses significant risks to safety, including maritime accidents and threats to navigational security. Therefore, an effective and integrated maritime traffic management system is essential. The ship reporting system (SRS) is one of the key navigational instruments that play a vital role in monitoring vessel movements in real-time by reporting dynamic information—such as position, course, and destination of ships—to authorized shore stations, such as coast radio stations (SROP) and vessel traffic services (VTS). This study aims to evaluate the effectiveness of SRS implementation in Indonesia using a quantitative approach through policy document analysis and field observations. Additionally, the study examines the utilization of the automatic identification system (AIS) and electronic navigational charts (ENCs) in supporting reporting functions and ensuring navigational safety. The findings indicate that human factors highly influence the success of the SRS, the quality of communication between ships and shore stations, and the integration of maritime information technology. These insights provide essential contributions to the formulation of strategic navigational policies that are adaptive to technological advancements and the evolving dynamics of shipping within the ALKI region.